New genera, new species and new records of leafhoppers (Hemiptera: Cicadellidae) from Vietnam - Dietrich, Christopher H.; Nguyen, Huong T. T.; Pham, Hong Thai (Zootaxa, 2020)
Recent collecting in northern Vietnam yielded specimens of several new leafhopper species, two of which represent new monotypic genera, and several additional species not previously recorded from Vietnam. The two new genera (Hochiminus n. gen. and Pseudocestius n. gen.) and 15 new species (Abrus digitatus n. sp., Aeternus ninhbinhensis n. sp., Drabescoides bispinosa n. sp., Tenompoella vietnamensis n. sp., Uzelina (Uzelina) vietnamensis sp. n., Hochiminhus tamdaoensis n. sp., Pseudocestius cucphuongensis n. sp., Phlogothamnus pseudorugosus n. sp., Scaphoidella albopunctata n. sp., Bundera onukiiformis n. sp., Carinata arcuata n. sp., Traiguma hamocauda n. sp., Signoretia tamdaoensis n. sp., Amrasca (Quartasca) curvata n. sp., Amrasca (Quartasca) excavata n. sp.) are described and illustrated and comparative notes are provided. An additional 28 species representing 20 genera are newly recorded from Vietnam. Most of the latter were previously recorded only from southern China. The enigmatic species, Tardrabassus pakneunensis Dai & Dietrich, previously known from two males collected in Laos in 1918, is newly recorded from Vietnam based on recently collected female specimens. The ovipositor structure of the female confirms placement of Tardrabassus in Iassinae. The female pregenital sternite and ovipositor of Hamulotettix ungulatus Dai & Zhang are also illustrated for the first time. A new synonymy is also proposed: Ujna consors Distant, 1908 equals Mileewa puerana Yang & Meng, 2010, n. syn.